Experimental study on mechanical properties of single fracture-hole red sandstone - Jiang, Ning; Lv, Ke; Gao, Zhiyou; Jia, Chuanbao; Ye, Lei; Meng, Shuyu; Su, Quanbao (Frontiers in Earth Science, 2023)
Various fractures and holes in the natural rock mass affected the mechanical properties of the rock mass and the safety construction of engineering. In this study, we investigated the mechanical properties of a single fracture-hole rock specimen using particle flow code 2D (PFC2D) numerical simulation software and through laboratory tests. We analysed the failure behaviours and mechanical properties of the rock specimen with a single fracture-hole specimen under different fracture angles. The failure modes of single fractured rock samples with different fracture angles were revealed. The fracture propagation and stress evolution of the rock specimen with a single fracture-hole under different fracture angles were investigated. The experimental results shown that the peak strength, peak strain, elastic modulus, initial fracture stress, and damage stress of the single fracture-hole rock specimen with different fracture angles were significantly less than those of the intact rock specimen. Moreover, fracture hole defects accelerated the generation of fractures and promote the failure of the rock specimen. The failure modes were divided into Y, inverted Y, and V types. Before the rock specimen fractures, the stress concentration area was mainly distributed at both ends of the fracture. The stress concentration area at both ends of the fracture gradually decreased, and the stress concentration area near the hole gradually increased as the fracture angle increased. By experiments, the acoustic emission of the model had gone through three stages: initial, steady growth, and rapid decline. The size of the inclination angle affected the number of acoustic emission hits and the generation of acoustic emission signals. Failure behaviours of the rock specimen with a single fracture-hole were systematically investigated, which could promoted the development of fracture rock mechanics and improved the understanding of instability failure mechanism in rock engineering, such as nuclear wasted treatment engineering and deep underground engineering.